Value-added in Public Service Innovation: The Practice at Integrated Service Units in Pontianak Municipality and Tanah Bumbu District (Jurnal Bina Praja, 2016)
The rise of innovations in the public sector creates something new in delivering public services. This study aims to analyze value-added in the practices of service innovation in the public sector. Drawing on desk research method, this study uses secondary data from literature sources. Innovation becomes a way to create value-added in public service sphere. This study concludes that some innovations created in the integrated service units in Pontiana Municipality and Tanah Bumbu District are included in innovation process which delivers efficiency and easiness values for the users of SITU, SIUP and TDP services. The innovation in the two service agencies has succeeded to reduce service delivery duration and minimized the occurrence of opportunity lost among citizens so that the innovation creates public value.Furthermore, those innovation practices demonstrate that there is an adjustment of network community governance in the process of public service administration.
Keywords: value-added; innovation; public service